The Impact of AI on App Monetization: Predictive Analytics for Revenue Growth - Srikanth Balla, (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The rapid expansion of the mobile app industry has led to a significant transformation in monetization strategies, with Artificial Intelligence (AI) playing a pivotal role in optimizing revenue generation. This paper investigates the impact of AI-driven predictive analytics on mobile app monetization, focusing on how AI technologies enhance user engagement, segmentation, and ad targeting to maximize revenue growth. By analyzing various AI applications, such as machine learning algorithms and deep learning models, the study explores their potential to predict user behaviors, personalize content, and optimize in-app purchases. The research employs a mixed-methods approach, combining case studies of successful AI-powered apps with quantitative data analysis of revenue growth. The findings suggest a strong positive correlation between AI implementation and increased revenue, especially through personalized marketing and predictive pricing models. The paper concludes by highlighting the challenges and limitations of integrating AI in app monetization, including data privacy concerns and the complexity of AI models. It emphasizes the need for app developers to adopt AI technologies for enhanced monetization strategies while addressing associated challenges.
Keywords: AI; Predictive Analytics; App Monetization; Revenue Growth; Machine Learning; User Segmentation; Personalized Marketing; Mobile Apps; In-App Purchases; Deep Learning; Artificial Intelligence in Apps